Decomposition heuristic for parallel-machine transfer line design with dual-uncertainties-based chance constraints. Issue 2 (1st February 2019) - He, Cong; Guan, Zailin; Luo, Dan; Fang, Weikang; Ullah, Saif
ABSTRACT: In this article, a new transfer line structure, the parallel-machine transfer line (PMTL), is studied. Compared to a traditional transfer line, PMTL is designed for high reliability due to its capacity for overdesign, by considering the uncertain failure of machines in the design. Dual uncertainties including the uncertain occurrence of machine failure and uncertain failure repair times are simultaneously considered in PMTL, and a chance-constrained programming (CCP) model is proposed for the uncertain PMTL design problem. A novel decomposition heuristic (DH) that is able to decompose the CCP into related sub-problems according to the relevance of the constraints is introduced, and linearization and transformation of the constraints are carried out to solve the sub-problems. Several experimental examples of uncertain PMTL design problems are prepared and solved by the DH and stochastic simulation, and the results show that DH outperforms the stochastic simulation with similar results but in a shorter computation time.